Antibacterial Potency of Combined Extracts of Mitragyna inermis (Linn) and Monotes kerstingii (Linn) on Salmonella Typhi and Salmonella Paratyphi A and Its In vivo Toxicity against Swiss Albino Mice - Zumbes, H.J.; Babalola, O.B.; Nanle, C.D.; Katnap, R.S.; David, E.V.; Anejo-Okopi, A.J.; Dabo, D.A.; Gokir, J.D.; Nvau, J.B. (UMYU Journal of Microbiology Research)
The phytochemical screening, antibacterial and toxicological effect of the extracts of Monotes kerstingii (Linn) and Mitragyna inermis (wild) extracts were investigated. The plant extracts were prepared by cold maceration method using water and ethanol and screened against Salmonella Typhi and Salmonella Paratyphy A using the agar well diffusion method. The LD50 of the extract was determined using Locke’s method. Phytochemical analysis reveals the presence of Carbohydrates, Cardiac glycosides, Steroids, Anthraquinones, Resins, Saponins, Flavonoids Tannins and Alkaloids in both plant extracts. The combined ethanol and aqueous plant extracts shows activity against S. Typhi with diameter of zones of inhibition ranging from 14.00 mm and 15-24 mm respectively. The combined extracts were also active against S. Paratyphi A with diameter of zones of inhibition ranging from 10-24mm and 11-26 mm for ethanol and aqueous extracts respectively. Toxicity studies of the combined extracts revealed that the plant was well tolerated at 5000mg/kg body weight. These results suggest that the plant may be exploited for therapeutic purposes.